Communication self-efficacy in optometry: the mediating role of mindfulness - Sundling, Vibeke; van Dulmen, Sandra; Eide, Hilde (Scandinavian Journal of Optometry and Visual Science, 2016)
The aim of this study was to examine the relationship between optometry students’ communication self-efficacy and their level of mindfulness and empathy. The study had a cross-sectional design. The sample included qualified optometrists in their first year of the Masters’ degree programme. The students reported level of communication self-efficacy, empathy and mindfulness by responding to three questionnaires: Ammentorp’s Clear-Cut Communication with Patients, Jefferson Scale of Empathy, and Mindful Attention Awareness Scale. Thirty-three students participated. The communication self-efficacy sum score was 111 (95% CI 106 to 116), the empathy sum score was 107 (95% CI 103 to 111) and the mindfulness sum score was 52 (95% CI 103 to 111). There was a significant positive correlation between communication self-efficacy and mindfulness (r = 0.295, n = 29, p = 0.029), but not between communication self-efficacy and empathy. Mindfulness correlates with communication self-efficacy. Mindfulness could therefore be important in training communication skills and could contribute to the effect of communication skills training. Most optometrists provide services in a retail setting, linking person-centred communication and care, evidence-based medicine, product technology and customer service. Further studies should explore how communication self-efficacy, explicit and tactic knowledge, empathy, mindfulness, emotional intelligence, patient satisfaction and customer service relate to communication and patientcentred care.